The feasibility and effectiveness of a streamlined single‐catheter approach for radiofrequency atrial fibrillation ablation. Issue 4 (26th June 2020) - Chin, Shui Hao; O'Brien, Jim; Epicoco, Gianluca; Peddinti, Prithvi; Gupta, Akanksha; Modi, Simon; Waktare, Johan; Snowdon, Richard; Gupta, Dhiraj
Abstract: Background: Catheter ablation for atrial fibrillation (AF) traditionally requires the use of circular mapping catheter (CMC) for pulmonary vein isolation (PVI). This study aimed to assess the feasibility and effectiveness of a CMC‐free approach for AF ablation performed by a contiguous optimized (CLOSE) ablation protocol. Methods: A CLOSE‐guided and CMC‐free PVI protocol with a single transseptal puncture was attempted in 67 patients with AF. Left atrial (LA) CARTO voltage mapping was performed with the ablation catheter pre‐ and postablation to demonstrate entry block into the pulmonary veins, and pacing maneuvers were used to confirm exit block. Results: The CMC‐free approach was successful in achieving PVI in 66 (98.5%) cases, with procedure time of 148 ± 32 minutes, ablation time of 27.5 ± 5.7 minutes, and fluoroscopy time of 7.8 ± 1.0 minutes. First‐pass PVI was seen in 58(86.5%) patients, and pacing maneuvers successfully identified the residual gap in eight of the other nine cases. No complication was observed. At 12 months follow‐up, 60 (89.6%) patients remained free from AF. The CMC‐free approach resulted in a cost saving of £47, 190. Conclusion: A CMC‐free CLOSE‐guided PVI approach is feasible, safe, and cost‐saving, and is associated with excellent clinical outcomes at 1 year. Abstract : Catheter ablation for atrial fibrillation traditionally requires the use of circular mapping catheter for pulmonary vein isolation. Using a contiguous (CLOSE protocol) and Ablation Index‐guided workflow, this study demonstrated that a single‐catheter approach is feasible, effective and cost‐saving, producing superior first‐pass isolation rate and 12‐month clinical outcome.